161k views
0 votes
(2 ÷ 12) - 32 + 4 × 8 - 33

User Maghoumi
by
5.3k points

2 Answers

5 votes

Answer:

222.92

Explanation:

(2 ÷ 12) - 32 + 4 × 8 - 33

ok lets simplify

0.1666 rounds up to 0.17

0.17 ÷ 12 = 0.01 (rounded up)

0.01 -32 = 31.99

31.99 + 4 = 35.99

35.99 x8 =255.92

255.92 - 33 = 222.92

WARNING: MIGHT BE INCORRECT OR OFF SLIGHTLY!

User Jayesh Kavathiya
by
5.6k points
7 votes

ANSWER


- (197)/(8)

EXPLANATION

The given expression is


(2 / 12) - 32 + 4 * 8 - 33

We simplify the parenthesis first to obtain:


(1)/(6) - 32 + 4 * 8 - 33

We now multiply to get,


(1)/(6) - 32 + 32- 33

Next, we add to get;


(1)/(6) - 33

We finally subtract by collecting LCD.


(1 - 198)/(6) = - (197)/(6)

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.